EPR : English proficiency for empowered professionals - Santillana, Priscilla Mizpah; Maranan, Anita C.; Reyes, Mercedita S.; Gamara, Amabella P.; Lepran, Julius Ceasar P.; Liwag, Angelica Fe A.; Ocampo, Jacqueline G.; Catequista, Kristine Amor S. (Mandaluyong City : Books Atbp. Publishing Corp., 2023)
This book will not only provide students with a comprehensive explanation of grammar rules, but it will also provide them with insightful examples, and practical exercises that will enable them to apply these rules.
Preface -- Lesson 1. Sentence and its parts -- 2. Sentence and its parts -- 3. Sentence types -- 4. Achieving consistency ideas -- 5. Achieving consistency in verb tense -- 6. Achieving consistency in verb mood -- 7. Achieving consistency in verb voice -- 8. Achieving consistency in language -- 9. Achieving consistency in person and number -10. Achieving coherence by avoiding misplaced and dancing modifiers -- 11. Achieving coherence by avoiding faulty parallelism -- 12. Achieving coherence by avoiding unclear reference of pronouns -- 13. Achieving emphasis through sentence variety -- 14. Paragraph writing -- References
Includes bibliographical references.
Keywords: ENGLISH LANGUAGE -- STUDY AND TEACHING